The interval between the emergence of pharmacologically synchronized ovarian follicular waves and ovum pickup does not significantly affect in vitro embryo production in Bos indicus, Bos taurus, and Bubalus bubalis - Gimenes, Lindsay U. [UNESP]; Ferraz, Marcio L.; Fantinato-Neto, Paulo; Chiaratti, Marcos R.; Mesquita, Ligia G.; Sa Filho, Manoel F.; Meirelles, Flavio V.; Trinca, Luzia A. [UNESP]; Renno, Francisco P.; Watanabe, Yeda F.; Baruselli, Pietro S. (Elsevier B.V., 2015)
The aim of the present study was to determine the optimal phase of the follicular wave to perform ovum pickup (OPU) for in vitro embryo production (IVEP) in various genetic groups. For this purpose, 27 heifers-nine Bos taurus (Holstein), nine Bos indicus (Nelore), and nine Bubalus bubalis (Mediterranean)-were maintained under the same nutritional, management, and environmental conditions. Heifers within each genetic group were submitted to six consecutive OPU trials with 14-day intersession intervals, at three different phases of the pharmacologically synchronized follicular wave (Day 1, 3, or 5 after follicular wave emergence), in a 3 x 3 crossover design. When OPU was performed at different phases of the pharmacologically synchronized follicular wave (Day 1, 3, or 5), no differences were found in the percent of oocytes recovered (70.5 +/- 3.1%, 75.0 +/- 3.1%, 76.0 +/- 3.2%, respectively; P = 0.41) or blastocyst production rates (19.4 +/- 2.9%, 16.6 +/- 2.9%, 15.9 +/- 2.6%, respectively; P = 0.36). Comparing genetic groups, B indicus showed a higher blastocyst rate (28.3(a) +/- 2.8%; P < 0.01) than B taurus and B bubalis (14.1(b) +/- 2.9% and 10.2(b) +/- 2.0%, respectively). However, only B indicus heifers showed a variation in the number of visualized follicles and the total and viable oocytes along consecutive OPU sessions. In conclusion, different phases of the pharmacologically synchronized ovarian follicular wave did not affect OPU-IVEP in B indicus, B taurus, and B bubalis heifers. Additionally, B indicus heifers showed greater OPU-IVEP efficiency than did the other genetic groups, under the same management conditions.
Keywords: Nelore; Holstein; Buffalo; Oocyte; Embryo